Responses of basil cultivars to irrigation water salinity - Maia, Sandra S. S.; Silva, Ricardo C. P. da; Oliveira, Francisco de A. de; Silva, Otaciana M. dos P. da; Silva, Ana C. da; Candido, Willame dos S. [UNESP] (Univ Federal Campina Grande, 2017)
The objective of this work was to verify the response of basil cultivars to the salinity of irrigation water during the period from January 15 to March 20, 2013, in a greenhouse, at the Federal Rural University of the Semi-Arid, Mossoro, RN, Brazil. The experimental design was completely randomized, with treatments arranged in 2 x 4 factorial scheme, constituted of two cultivars of basil ('Verde' and 'Roxo') and four levels of irrigation water salinity (0.5; 2.0; 3.5 and 5.0 dS m(-1)), with four replicates. The plants were collected at 65 days after transplanting and the following variables were evaluated: stem diameter; plant height; number of stems and leaves; leaf area; dry matter of leaves, stems, roots, and total dry matter. The increase in salinity was detrimental to all variables evaluated in both cultivars, but the cultivar 'Roxo' proved to be more tolerant than the cultivar 'Verde'. Both cultivars are tolerant to irrigation water salinity of up to 1.5 dS m(-1).
Keywords: Ocimum basilicum L.; salt stress; medicinal plants